2015
DOI: 10.1186/s12916-015-0458-5
|View full text |Cite
|
Sign up to set email alerts
|

Repeat HIV-testing is associated with an increase in behavioral risk among men who have sex with men: a cohort study

Abstract: BackgroundThe Center for Disease Control and Prevention recommends that high-risk groups, like sexually active men who have sex with men (MSM), receive HIV testing and counseling at least annually. The objective of this study was to investigate the relationship between voluntary repeat HIV testing and sexual risk behavior in MSM receiving rapid serologic and nucleic acid amplification testing.MethodsWe performed a cohort study to analyze reported risk behavior among MSM receiving the “Early Test”, a community-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
2
44
0
2
Order By: Relevance
“…This practice may be relatively insensitive in settings where MSM undergo HIV screening frequently ( 11 ). Our results show that expansion of AHI screening to include those with signs or symptoms during the 2 weeks before the test may increase the yield of AHI diagnoses by more than half.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice may be relatively insensitive in settings where MSM undergo HIV screening frequently ( 11 ). Our results show that expansion of AHI screening to include those with signs or symptoms during the 2 weeks before the test may increase the yield of AHI diagnoses by more than half.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this confidential HIV testing program, routine, individual donation, HIV nucleic acid amplification testing (NAT) has been provided to all rapid antibody–negative participants since June 2007 (samples for NAT are obtained at the time of rapid antibody testing) ( 7 , 10 , 11 ). AHI was defined as having a negative or indeterminate HIV antibody test result in the presence of detectable HIV-1 RNA, corresponding to Fiebig stages I–II, with a mean estimated date of infection within the previous 10 days (95% CI 7–14 days) ( 12 ).…”
Section: The Studymentioning
confidence: 99%
“…29,37 In a cohort study of MSM living in San Diego, California, MSM who reported more than 10 male partners and condomless receptive anal intercourse was associated with higher rates of repeat testing. 45 Testing associated with a high-risk sexual behavior such as CAI may lead to justification of that behavior by the individual if the test results are continuously negative, increasing the risk of HIV transmission. 36 This is especially important when considering offering high-risk MSM self-tests such as OraQuick, which has a large window period.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were MSM who reported sexual contact with men during the 12 months prior to testing. Basic demographics, risk behaviors, and frequency of repeat HIV testing from this cohort have been published previously [20][21][22]. An estimated date of infection was calculated for all recently infected persons using previously published criteria for serologic and virologic test results [23].…”
Section: Methodsmentioning
confidence: 99%